Daily life of deported Kalmyks in the Ishim district of Omsk (Tyumen) regions - A. A. Frolova (Омский научный вестник: Серия "Общество. История. Современность")
The article examines the features of the daily life of Kalmyks in the conditions of special settlement on the territory of the Ishim district of the Omsk/Tyumen regions. On the basis of the office documentation of state authorities and special services, materials of oral history, the daily practices and everyday organization of the life of the deported Kalmyk population are considered. The authors conclude that regional specificity is a significant factor determining the patterns of the deported population’s exit from crisis situations.